Molecular dynamics study of bimetallic Fe–Cu Janus nanoparticles formation by electrical explosion of wires. Issue 9 (3rd May 2019) - Tsukanov, A. A.; Lozhkomoev, A. S.; Lerner, M. I.; Gotman, I.; Gutmanas, E. Y.; Psakhie, S. G.
ABSTRACT: Bimetallic nanoparticles comprised of two elements which are immiscible in the bulk present a unique combination of physical–chemical properties that strongly depend on the atomic arrangement within the particle. In this study, molecular dynamics (MD) simulations of bimetallic Fe–Cu nanoparticles formation by high-velocity collision of individual metal nanoparticles (IMNPs) were performed. Physically these conditions model fast electrical explosion of two metal wires (Fe and Cu). By varying the size, temperature and velocity of colliding IMNPs, the conditions under which phase-segregated Janus nanoparticles are formed were determined. The model predictions showed good agreement with the experimental results. The present work is a step forward to understanding the formation mechanisms of bimetallic nanoparticles with different chemical configurations.